A REVIEW ON PENETRATION ENHANCER FOR SEMISOLIDS - Sonje, Abhijit; Thube, Rahul; Parmar, Vishal; Kumari, Gini; Deshpande, Prajakta (Asian Journal of Pharmaceutical Research and Development, 2013)
There is considerable interest in the skin as a site of drug application both for local and systemic effect Semisolids dosage forms usually are intended for localized drug delivery. In the past few years, however, these forms also have been explored for the systemic delivery of various drug candidates who’s per oral bioavailability is questionable. Several novel drugcarrier systems have been examined that offer enhanced release, controlled release, or a stable environment for the incorporated drug. A recent advance in semisolid dosage form allows modified release as well as flexibility in route of administration. However, the skin, in particular the stratum corneum, poses a formidable barrier to drug penetration thereby limiting topical and transdermal bioavailability. Skin penetration enhancement techniques have been developed to improve bioavailability and increase the range of drugs for which topical and transdermal delivery is a viable option. This review describes enhancement techniques based on drug/vehicle optimisation such as Selection of correct drug or prodrug, Chemical potential adjustment, Ion pairs and complex coacervates, Eutectic systems, Hydration, Chemical penetration enhancers, Microneedle array, Stratum corneum ablated, Follicular delivery, Ultrasound, Iontophoresis, Electroporation, Magnetophoresis, Pressure wave, Liposomes and other vesicles, Niosomes, Transfersomes. The mechanism of action of chemical penetration enhancers and their potential for clinical application is described.